Cuckoo search algorithm as an optimizer for optimal reactive power dispatch problems - M. H., Sulaiman; Zuriani, Mustaffa (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents the application of Cuckoo Search Algorithm (CSA) in optimizing the control variables of power system operation in solving the optimal reactive power dispatch (ORPD) problem. CSA is inspired by the parasitic behavior of Cuckoo birds in reproduction process based on the probability for a host bird in discovering an alien egg in its nest. The implementation of CSA in determining the optimal value of control variables such as generator bus voltages, transformer tap setting and shunt reactive elements in order to obtain the minimize loss in the system. In this paper, IEEE-30 bus system is utilized to show the effectiveness of CSA and then the comparison with other nature inspired algorithms will be presented.